Paciente de 69 años de edad de sexo masculino con enfisema pulmonar. - Alcívar Baquerizo, Ronald Alexander (2020)
The clinical case studied has the following structure: as an introduction, emphysema is an irreversible destructive disease of the alveolar walls due to the enlargement of the structures related to the uptake of air for the proper functioning of the lungs, such as the alveolar sacs, which they fill with air excessively due to total or partial inability to insufflate the air adequately, either due to deficiency of Alpha-1 Antitrypsin (AAT), accumulation of protease or due to the destruction of the elastic fibers of the alveolus secondary to oxidants that it releases tobacco smoke, our work has a theoretical support with the following topics: concept and pathological characteristics of emphysema, Risk factors, Evaluation of the patient with emphysema, and other topics based on our clinical case, as main objective we have to identify the treatment optimal to reduce the symptoms of pulmonary emphysema, which will be confirmed with the He gave our case in chapter 2 in the diagnostic methodology, once the case has been studied we can express the following conclusion that the optimal treatment to reduce the symptoms of pulmonary emphysema is the application of oxygen therapy and the application of metered dose inhaler therapy.